Inhibitory Effect of MicroRNA-107 on Osteosarcoma Malignancy Through Regulation of Wnt/β-catenin Signaling in Vitro. (16th March 2018) - Yu, Miao; Guo, Danqing; Cao, Zhenglin; Xiao, Longyi; Wang, Gang
GRAPHICAL ABSTRACT: ABSTRACT: We showed that miR-107 expression was decreased in osteosarcoma (OS) tissues and cell lines. miR-107 mimic significantly decreased OS cell proliferation and inhibited invasion and migration of OS cells. Inhibition of miR-107 expression notably promoted proliferation, invasion and migration of OS cells. In addition, miR-107 mimic inhibited EMT biomarkers and significantly increased apoptosis. miR-107 mimic significantly decreased the protein expression of β-catenin, Cyclin D1, and c-Myc, whereas increased GSK-3β protein expression. miR-107 mimic markedly reduced the luciferase activity of 3′UTR of β-catenin. Overexpression of β-catenin inhibited miR-107 mimic-induced decrease of cell proliferation, invasion and migration ability, and increase of apoptosis.